2004
DOI: 10.1182/blood-2003-10-3448
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-biased hematopoietic stem cells have extensive self-renewal capacity but generate diminished lymphoid progeny with impaired IL-7 responsiveness

Abstract: IntroductionHematopoietic stem cells (HSCs) are capable of generating mature cells of all the hematopoietic lineages. Self-renewal capacity, the ability to proliferate without differentiation, is a similarly important hallmark of HSCs. The undifferentiated status of HSCs is characterized by promiscuous expression of genes, many of which were thought to be lineage specific. [1][2][3] Commitment to differentiation increasingly limits the developmental potential of the original HSCs by regulating the level of exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
219
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(239 citation statements)
references
References 49 publications
(58 reference statements)
15
219
0
1
Order By: Relevance
“…Overall, our data are consistent with behavioral features of individual HSC clones being established in development prior to young adulthood and persistently manifest under varying conditions. Lineage bias and proliferative potency has been demonstrated previously (Dykstra et al, 2007;Morita et al, 2010;Muller-Sieburg et al, 2004;Picelli et al, 2013), including at the clonal level (Sun et al, 2014b). The data here indicate that multiple other characteristics including sensitivity to inflammation or radiation are also clone-specific features.…”
Section: Discussionsupporting
confidence: 74%
“…Overall, our data are consistent with behavioral features of individual HSC clones being established in development prior to young adulthood and persistently manifest under varying conditions. Lineage bias and proliferative potency has been demonstrated previously (Dykstra et al, 2007;Morita et al, 2010;Muller-Sieburg et al, 2004;Picelli et al, 2013), including at the clonal level (Sun et al, 2014b). The data here indicate that multiple other characteristics including sensitivity to inflammation or radiation are also clone-specific features.…”
Section: Discussionsupporting
confidence: 74%
“…We found that My-bi HSC give rise to normal myeloid progeny but their lymphoid progeny showed a blunted response to Interleukin-7. 2 This lymphokine is central for the differentiation and homeostatic proliferation of lymphoid cells. 39,40 Analogously, Ly-bi HSC have an impaired ability to generate myeloid progeny.…”
Section: Lineage-biased Hsc-a Paradigm Of Epigenetically Fixed Hsc Bementioning
confidence: 99%
“…Myeloid-biased (My-bi) HSC give rise to too few lymphocytes, and lymphoid-biased (Ly-bi) HSC generate too few myeloid cells. 2 All three types are normal HSC in that they have self-renewal capacity and can regenerate all hematopoietic lineages (pluripotency). Strikingly, the lineage bias is preserved through multiple rounds of serial transplantation: balanced HSC self-renew to give rise to daughter HSC that are also balanced, My-bi HSC give rise to My-bi daughter HSC, and Ly-bi produce Ly-bi daughter HSC.…”
Section: Lineage-biased Hsc-a Paradigm Of Epigenetically Fixed Hsc Bementioning
confidence: 99%
See 2 more Smart Citations